Imprinting Chirality on a Conventional Superconductor. Issue 4 (15th January 2023) - Sukenik, Nir; Ozeri, Meital; Gutfreund, Alon; Fridman, Nofar; Noah, Avia; Yochelis, Shira; Remennik, Sergei; Anahory, Yonathan; Millo, Oded; Paltiel, Yossi
Abstract: Chiral imprinting is demonstrated in metals, semiconductors, and oxides. In these cases, the mixing of chiral molecules with the studied material changes the structure of the hybrid system, resulting in new physical properties. In this work, chirality is imprinted on lead (Pb) that is a conventional singlet s‐wave superconductor. The hybrid material exhibits an increase in the critical field ( H C ) and a wider temperature phase transition under in‐plane magnetic fields. These results demonstrate a method for locally altering the magnetic‐response properties of conventional superconductors. Abstract : Chiral imprinting is demonstrated in metals, semiconductors, and oxides. Here, chirality, a superconductor, is imprinted on lead by evaporation onto a chiral monolayer. The hybrid material exhibits an increase in the critical magnetic field, thus demonstrating a method for locally altering the magnetic response of superconductors. This alteration has great importance in superconducting circuits sensitive to magnetic fields such as superconducting Q‐bits.